ANALISA FAKTOR PENYEBAB KERUSAKAN JALAN KELAS IIIA DI KABUPATEN LAMONGAN - Muhammad Maftukin; Dwi Kartikasari (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2017)
Road  damage  sometimes  occurs  earlier than  the  period  of  service  caused  by  many  factors, among  others  are  human  factors  and  natural  factors.  With  the  growing  number  of  vehicles,it  is possible that the road would be damaged in a relatively short time. The purpose of this study is to know the effect of vehicles volume with the level of road damage and the relationship between the vehicles volume  with the level of road damage. In research method, there are several steps that must be done in order to get the results of research that includes doing a preliminary study to knowthe  characteristics  of  the  roads.  This  research  was  conducted  in  the  segment  of  Sekaran  Raya Road, Laren  Raya  Road,  Solokuro  Raya  Road,  and Blimbing  Paciran  Raya  Road  with  the  road damage score amounted to 80.2; 85.2; 86.2 and 80.2 respectively. The traffic volume at peak hours respectively  amounted  3,375.5  smp/hour,  3,320.2  smp/hour,  2,053.9  smp/hour  and  3,832.7 smp/hour.  It  is  known  from  the  result  of  the  traffic  volume  regression  that  the  road  and  time damage  score  is  y  =  0,002824883.x1  +  0,001498059.x2  +  77.00509615,  with  non-linear regression (R2) or the correlation between the x variables with y is = 0.617977513, that the  higher the traffic volume then the road damage will be even greater.